Historical examination of tuberculosis; from ancient affliction to modern challenges - Seyyed Mohammad Amin Mousavi-Sagharchi; Atousa Ghorbani; Maryam Meskini; Seyed Davar Siadat (Journal of Infection and Public Health, 2025)
Tuberculosis (TB), white plague, many other definitions is an ancient deadly infection that humans dealt with after creation. The first hypothesis refers to 150 million years ago about the appearance of TB in the Jurassic era before human creation, but documents show 9000 years ago for first appearance in human society. In 1882, Robert Koch was able to identify and describe the best possible agent of TB. After the discovery of TB’s agent [Mycobacterium tuberculosis], progress was made in diagnosis and treatment rapidly, and invasive operations such as surgery were replaced with drug treatment and chemical compounds hired for treatment that were so effective before drug resistance occurrence. In this review authors done their tries to describe all aspects of TB [identification, epidemics, diagnostics, drug development, etc.] in history from ancient records to the present condition and give insight into the future of TB ending in 2030 and 2050.